Risk Factors for Acute Respiratory Infection in Children Under Five in Padang, Indonesia - Hidayanti, Rahmi; Yetti, Husna; Putra, Andani Eka (Journal of Maternal and Child Health, 2019)
Background: Acute Respiratory Infection (ARI) is a major cause of acute diseases and death in infants worldwide. Percentage of ARI (year 2017) in children aged 12-59 months in Padang was 26.5% and Andalas health center was 33.2%. ARI is influenced by many factors such as environmental condition. This study aimed to analyze risk factors for ARI in children under five in Padang, Indonesia.Subjects and Method: This was a case control study conducted at Andalas community health center, Padang, Indonesia. A sample of 90 children aged 12-59 months was selected for this study. The dependent variable was ARI. The independent variables were humidity, house ventilation, dwelling density, indoor smoke cigarette. Data on ARI status were taken from medical record. The other variables were measured by questionnaire and observation sheet. The data were analyzed by a multiple logistic regression.Results: Poor ventilation (OR = 11.73; 95% CI = 2.16 to 63.86; p = 0.004), high dwelling density (OR = 21.99; 95% CI = 3.75 to 129.04; p = 0.001), indoor cigarette smoke (OR = 5.09; 95 % CI = 1.06 to 24.34; p = 0.042), and high air humidity (OR = 5.00; 95% CI = 0.79 to 31.51; p = 0.086) increased the risk of ARI in children under five and they were statistically significant.Conclusions: Poor ventilation, high dwelling density, indoor cigarette smoke, and high air humidity increase the risk of ARI in children under five.Keywords: Acute respiratory infection, dwelling density, air humidity, children under fiveCorrespondence:Rahmi Hidayanti. Masters Program in Public Health, Faculty of Medicine, Universitas Andalas Padang. Jl. Perintis Kemerdekaan Padang, Indonesia. Email: rahmi.hidayanti@yahoo.com. Mobile: +6281363467226Journal of Maternal and Child Health (2019), 4(2): 62-69https://doi.org/10.26911/thejmch.2019.04.02.01